SEASONAL RESPONSES OF TWO FAUNAL TAXA TO FIRE TREATMENTS IN YANKARI GAME RESERVE, NIGERIA (FULafia Journal of Science and Technology, 2016)
The custom of using fire as a management tool in protected areas needs to be within a frame work of an understanding of the responses of biodiversity. This is to avoid or reduce the negative impacts of ecological disturbances in an ecosystem. More responses of floral than faunal components of biodiversity to fire have been studied and reported.This study was aimed at determining the faunal responses to fire in both wet and dry seasons at the Yankari Game Reserve (YGR)located in lat10° 30’ E and long 9° 45’ N. The birds andinsects were used in the study to bridge the knowledge gap of fire ecology in Nigeria. Point transects treated with late burns during the wet season (April to June) and early burns during the dry season (November) were used to record birds and insects. Data was collected from 37 points in the wet season and from 45 points in the dry season. Results show that fire had a significant effect on insect abundance during the wet season and there was also a significant difference between mean insect diversity in wet and dry seasons and a higher bird and insect abundance and diversities was observed in wet than in dry season. The early burn fire regime is therefore, recommended as a fire treatment regime in the YGR. The need for conservation managers to maintain equilibrium between management practices and population dynamics in ecosystems is further highlighted
Keywords: Fire; abundance; diversity; insects; birds; Reserve